Рафинирование Cd и Zn от примесей внедрения при дистилляции с геттерным фильтром ZrFe - Kondrik, A. I.; Solopikhin, D. A.; Scherban', A. P. (PE "Politekhperiodika", Book and Journal Publishers, 2013)
Behaviour of interstitial impurities in Cd and Zn is analysed in terms of thermodynamics. The authors consider reduction reactions of cadmium, zinc and carbon oxides, as well as zinc nitride with the getter material from the Zr–Fe alloy, depending on temperature and vacuum. Optimum initial temperature and vacuum conditions for the processes of deep refining of Cd and Zn from interstitial impurities has been developed. It has been shown experimentally that the proposed refining method provides a more effective cleaning of cadmium and zinc from the interstitial impurities than the distillation without a filter: the impurity content is reduced more than tenfold compared to the concentration in the input metal.